Fire safety management in condominium (tenants knowledge and prepardness) / Mohammed Mazly Mohammed Mahmud - Mohammed Mahmud, Mohammed Mazly (Faculty of Architecture, Planning and Surveying, 2010)
Staying or working in high rise buildings comes with a great risk. A preparedness action should be taken to face the risk of fire in high rise residential buildings, a fire safety program that have been done need to have full support from tenants. A good fire safety program need to be manage by a good management. This can be done by implementing and adapting all necessary action. This program can help tenants to act during fire and know what to do on fire. Knowledge of equipment and knowledge on react is both important to ensure safety and properties.